Anticancer Effects of Copper(II) Complexes Hydrazone −Based Schiff Base: A review - Roghayeh Fekri (Basic & Clinical Cancer Research, 2022)
Cancer treatment has traditionally been comprised of established treatments such as radiation, surgical excision, and chemotherapy, which can be used alone or in combination. Many therapeutic factors have been extracted from minerals, plants, and animals, the majority of them have been synthesized in the lab, making them a valuable source of innovation pharmacologically. Due to the in vitro cytotoxic effect of metal complexes, the interest in these compounds increases day by day in cancer treatment. The electronic nature of metals, modifications in ligands, and conformational changes in functional groups give rise to the discovery of drugs with different cytotoxic and pharmacokinetic properties. In recent decades, the number of persons receiving chemotherapy has increased considerably. Medicinal inorganic chemistry can take advantage of the unique properties of metal ions to generate new drugs. This has prompted chemists to use various approaches creating novel metal-based anticancer drugs with various mechanisms of action, which are significant in the pharmaceutical industry due to their potent anticancer properties. Schiff base ligands and transition metals are the most researched coordination chemicals. Their applications as anticancer medicines are becoming more significant. This research analyzes various publications linked to copper complexes based on Schiff base hydrazone ligand in cancer treatment, and this review will analyze publications on these compounds' anticancer qualities.